A North American Indigenous Narrative-based Inquiry of Culture and Land - Pitt, Jonathan (International Journal of Culture and History, 2024)
This research uses a narrative cultural inquiry study to address the need to save the land our Mother Earth (Aki) and the relationship with Indigenous Spirituality through the topics/themes of Spirit Houses, Sa’be (Sasquatch) and Sacred landscape features such as Spiritual Sites, Ceremony and Pictographs within the geography of Turtle Island, North America in Northern Ontario, Canada. The rationale of this study was to address the larger inaadiziwin (philosophy) of Indigenous character and way of life with nature or “All My Relations” for the author.